Impact of reinfection with SARS-CoV-2 Omicron variants in previously infected hamsters - Shiwa-Sudo, Nozomi; Sakai, Yusuke; Iwata-Yoshikawa, Naoko; Watanabe, Shinji; Yamada, Souichi; Kuroda, Yudai; Yamamoto, Tsukasa; Shirakura, Masayuki; Fujisaki, Seiichiro; Miyazaki, Kaya; Miura, Hideka; Nagata, Shiho; et al. (bioRxiv, 2022)
The diversity of SARS-CoV-2 mutations raises the possibility of reinfection of individuals previously infected with earlier variants, and this risk is further increased by the emergence of the B.1.1.529 Omicron variant. In this study, we used an in vivo, hamster infection model to assess the potential for individuals previously infected with SARS-CoV-2 to be reinfected with Omicron variant and we also investigated the pathology associated with such infections. Initially, Syrian hamsters were inoculated with a lineage A, B.1.1.7, B.1.351, B.1.617.2 or a subvariant of Omicron, BA.1 strain and then reinfected with the BA.1 strain 5 weeks later. Subsequently, the impact of reinfection with Omicron subvariants (BA.1 and BA.2) in individuals previously infected with the BA.1 strain was examined. Although viral infection and replication were suppressed in both the upper and lower airways, following reinfection, virus-associated RNA was detected in the airways of most hamsters. Viral replication was more strongly suppressed in the lower respiratory tract than in the upper respiratory tract. Consistent amino acid substitutions were observed in the upper respiratory tract of infected hamsters after primary infection with variant BA.1, whereas diverse mutations appeared in hamsters reinfected with the same variant. Histopathology showed no acute pneumonia or disease enhancement in any of the reinfection groups and, in addition, the expression of inflammatory cytokines and chemokines in the airways of reinfected animals was only mildly elevated. These findings are important for understanding the risk of reinfection with new variants of SARS-CoV-2. Competing Interest Statement The authors have declared no competing interest. Footnotes * Add the Supplemental Materials